Image guidance doses delivered during radiotherapy: Quantification, management, and reduction: Report of the AAPM Therapy Physics Committee Task Group 180. Issue 5 (24th March 2018) - Ding, George X.; Alaei, Parham; Curran, Bruce; Flynn, Ryan; Gossman, Michael; Mackie, T. Rock; Miften, Moyed; Morin, Richard; Xu, X. George; Zhu, Timothy C.
Abstract : Background: With radiotherapy having entered the era of image guidance, or image‐guided radiation therapy (IGRT), imaging procedures are routinely performed for patient positioning and target localization. The imaging dose delivered may result in excessive dose to sensitive organs and potentially increase the chance of secondary cancers and, therefore, needs to be managed. Aims: This task group was charged with: a) providing an overview on imaging dose, including megavoltage electronic portal imaging (MV EPI), kilovoltage digital radiography (kV DR), Tomotherapy MV‐CT, megavoltage cone‐beam CT (MV‐CBCT) and kilovoltage cone‐beam CT (kV‐CBCT), and b) providing general guidelines for commissioning dose calculation methods and managing imaging dose to patients. Materials & Methods: We briefly review the dose to radiotherapy (RT) patients resulting from different image guidance procedures and list typical organ doses resulting from MV and kV image acquisition procedures. Results: We provide recommendations for managing the imaging dose, including different methods for its calculation, and techniques for reducing it. The recommended threshold beyond which imaging dose should be considered in the treatment planning process is 5% of the therapeutic target dose. Discussion: Although the imaging dose resulting from current kV acquisition procedures is generally below this threshold, the ALARA principle should always be applied in practice. Medical physicists should make radiation oncologists aware of the imaging doses delivered to patients under their care. Conclusion: Balancing ALARA with the requirement for effective target localization requires that imaging dose be managed based on the consideration of weighing risks and benefits to the patient.